1990
DOI: 10.1056/nejm199003223221232
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Report of the Stroke Prevention in Atrial Fibrillation Study

Abstract: Atrial fibrillation, even in the absence of rheumatic valvular disease, predisposes patients to embolic complications, but the role of antithrombotic therapy in the prevention of such complications has not been fully clarified. We therefore performed a randomized, placebo-controlled trial to evaluate warfarin and aspirin individually as prophylaxis against ischemic stroke and systemic embolism (the primary events) in such patients. Patients eligible to receive warfarin (group 1) were assigned to warfarin (open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Prospective randomized studies from the late 1980s reported a dramatic and highly significant reduction in stroke in patients with AF treated with warfarin. The randomized AFASAK, 50 SPAF, 51 and BAATAF 52 studies were among the first to demonstrate that dose-adjusted warfarin prevented strokes effectively in patients with AF, confirmed in a later meta-analysis 53 …”
Section: Patients With Atrial Fibrillation Including Those With Paromentioning
confidence: 92%
“…Prospective randomized studies from the late 1980s reported a dramatic and highly significant reduction in stroke in patients with AF treated with warfarin. The randomized AFASAK, 50 SPAF, 51 and BAATAF 52 studies were among the first to demonstrate that dose-adjusted warfarin prevented strokes effectively in patients with AF, confirmed in a later meta-analysis 53 …”
Section: Patients With Atrial Fibrillation Including Those With Paromentioning
confidence: 92%
“…In those who already had sustained a fracture, especially at the hip, serum vitamin K concentrations have been found to be lower than in age-matched controls [16,17,18,19]. However, warfarin therapy has been demonstrated to reduce the risk of both primary and secondary ischemic strokes from nonrheumatic atrial fibrillation (NRAF) [20,21,22,23,24,25,26,27]. Such oral anticoagulation would seem likely to affect bone metabolism by interference with γ-carboxylated glutamyl acid protein synthesis in bone.…”
Section: Introductionmentioning
confidence: 99%
“…In each of these situations, INR should be maintained between (2.0 and 3.0). In MVP patients with AF, warfarin therapy is indicated in patients aged greater than 65 years and in those with mitral regurgitation, hypertension, or a history of heart failure (INR 2.0 to 3.0) [105, 106]. Daily aspirin therapy is often recommended for patients with high-risk echocardiographic characteristics.…”
Section: Valvular Heart Diseasesmentioning
confidence: 99%